A Cross-Generational Da’wah Strategy for Fostering an Understanding of Islam Among Generation Y and Generation Z in Aceh - Jasafat Jasafat; Syahril Furqany; Syamira Balqis; Syukri Syamaun; Ridwan Muhammad Hasan (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, Yogyakarta, Indonesia, 2026)
The transformation of da'wah media has become a central issue in the dynamics of religious life across generations in Aceh, especially between Generation Y (millennials) and Generation Z, which has not been seen in da'wah. The striking differences in the patterns of understanding and practising Islam between the two generations indicate communication challenges and the need for da'wah strategies to bridge these differences effectively. Generation Y tends to access Islamic teachings through traditional channels such as dayah and study religion, and adheres to the authority of local ulama. Meanwhile, Generation Z forms an understanding of Islam through social media, digital da'wah, and